2013
DOI: 10.1111/evj.12020
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exercising video‐endoscopic examination of the upper airway following laryngoplasty surgery: A prospective cross‐sectional study of 41 horses

Abstract: When investigating cases of ongoing respiratory noise or poor performance following LP, exercising endoscopy must be considered. Continued respiratory noise may be associated with poor arytenoid abduction and not performing concurrent ventriculectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 34 publications
4
46
2
3
Order By: Relevance
“…Following LP and VCE, collapse of vocal cord remnants occurred in 23% of horses in this study and has been reported elsewhere [5][6][7]21], highlighting the importance of complete vocal fold resection. Furthermore, it demonstrates the value of DRE as part of a complete and thorough evaluation of outcome following upper airway surgery.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Following LP and VCE, collapse of vocal cord remnants occurred in 23% of horses in this study and has been reported elsewhere [5][6][7]21], highlighting the importance of complete vocal fold resection. Furthermore, it demonstrates the value of DRE as part of a complete and thorough evaluation of outcome following upper airway surgery.…”
Section: Discussionsupporting
confidence: 78%
“…Almost half of the cases (48%) had ADAF post operatively concurring with the reported prevalence rates of 34-60% post LP [5][6][7]. Interestingly, horses were significantly more likely to have ADAF post LP compared with preoperatively, suggesting the surgical procedure may have a causative role in the development of ADAF, or that onset of the disease process occurs in the time frame between both exercising examinations.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We, therefore, believe that the improved exercising grades obtained after surgery in our study were due to the reinnervation. Several other studies in which resting and exercising endoscopy post-laryngoplasty were compared revealed a loss of arytenoid abduction during exercise compared with the resting abduction in 21% [20], 37% [22] and 45% [23] of the horses investigated, which was not observed in our study. In exercising grade C, the left arytenoid is less abducted than in the natural resting position [14] and, logically, this restricts airway flow.…”
Section: Discussioncontrasting
confidence: 77%
“…In recent papers describing exercising endoscopy post-laryngoplasty, DUAO was observed in 37-58% of cases [22,23]. After reinnervation surgery, horses may have low resting abduction grades because the C1/C2 nerve is only activated during forced respiration.…”
Section: Discussionmentioning
confidence: 99%